Actual Problems of Statutory Limitation Period Institution Enforcement - A. A. Aleshkin (Сибирское юридическое обозрение, 2012)
The article is devoted to some actual problems of statutory limitation period institution enforcement, specifically it is about the possibility of plaintiff to submit the missed limitation period application either in the court of the first instance or in the court of appeal.